Adaptation and psychometric analysis of the Malay version-Cultural Intelligence Scale (CQS) in Malaysia: the International Test Commission approach = Adaptasi dan analisis psikometrik Skala Kecerdasan Budaya (CQS) versi Bahasa Melayu di Malaysia: pendekatan Suruhanjaya Ujian Antarabangsa (ITC) - Harun, Mohd Ferdaus; Amru Iskandar, Afnan Safiyyah; Ahmad, Nur Amirah Husna; Shaukany, Muhammad Shameer Ezany; Mohd Hanafi, Muhammad Danial Akasyah; Shuhairi, Alisa Safiya (Penerbit UTM Press, 2025)
Cross-cultural interaction has become a necessity in the era of globalization, particularly in multicultural nations such as Malaysia. However, the absence of a valid and reliable psychometric instrument in the Malay language to measure cultural intelligence poses significant challenges for research and practical application. To address this gap, the present study aimed to translate, adapt, and evaluate the psychometric properties of the Malay version of the Cultural Intelligence Scale (CQS) in accordance with the ITC Guidelines (2017). The adaptation process employed a Sequential Translation Design, which included forward–backward translation, a committee approach, expert panel review, and empirical validation using survey data from N = 431 Malaysian respondents. Data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess factor structure, reliability, and construct validity. Findings revealed that the original four-factor structure of the CQS (metacognitive, cognitive, motivational, and behavioral) was retained. All reflective and formative measurement indicators met the standards of Confirmatory Composite Analysis (CCA). Furthermore, convergent validity was supported through significant positive correlations with the Tromsø Social Intelligence Scale, while discriminant validity was found through weak negative correlations with the Social Interaction Anxiety Scale. Overall, the results demonstrate that the Malay version-CQS is a valid and reliable instrument for assessing cultural intelligence in Malaysia. The study reinforces evidence that Cultural Intelligence is a higher-order construct which is stable across cultures. Practically, the instrument provides a strong foundation for applications in education, organizational training, and social integration policies, while strategically enhancing intercultural competence, social harmony, and national competitiveness.